Technical evaluation of kVar import anomalies on main transformer number 2 at Siman Hydroelectric - Mohamad Farel Firmansyah; Arya Kusumawardana; Royb Fatkhur Rizal; Soraya Norma Mustika; Hafidz Malkanz Chaironi; Ruth Nike Dauhan (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
An issue of reactive power import (negative kVar) was identified in Main Transformer No. 2 at PLTA Siman, resulting from mismatched voltage ratios and impedance values among parallel-operated transformers. This mismatch induced a circulating current and led to reactive power being absorbed from the external grid, increasing energy losses and operational costs. This study aims to investigate the root cause of the anomaly, propose technical solutions, and evaluate their effectiveness. The analysis was conducted out through system simulation using ETAP software, testing three technical scenarios: installation of a 569.9 kVar capacitor bank, implementation of a Standard Operating Procedure (SOP) for PMT disconnection during standby conditions, and replacement of the transformer with one that matches the specifications of the other units. The simulation results revealed that SOP implementation eliminated kVar import by 100% during standby, the capacitor bank reduced it by approximately 70%, and transformer replacement fully eliminated the circulating current. The findings suggest that a combined approach involving SOP and capacitor installation offers an optimal solution without major infrastructure replacement.